ANALISIS ABILITY TO PAY AND WILLINGNESS TO PAY JASA KERETA API YOGYAKARTA INTERNATIONAL AIRPORT - Imam Basuki; Steven Chuadinata (JURNAL SPEKTRAN, 2019)
The distance of Yogyakarta International Airport airport to Yogyakarta city ranges from 45 km. The train is one of the connectivity options towards the center of Yogyakarta's activities. In determining the transportation rates of people by train, it is necessary to consider the ability and willingness of train service users to pay a sum of money for the services provided. Because the value of Ability To Pay (ATP) and Willingness To Pay (WTP) affects the level of interest of service users. Questionnaire and interview methods were conducted to 130 respondents who were air transport users at Adisutjipto International Airport as a passenger approach at Yogyakarta International Airport. This study aims to determine the value of Ability To Pay (ATP) and Willingness To Pay (WTP) users of Railway services Yogyakarta - Yogyakarta International Airport. The results of the analysis show that the Ability To Pay (ATP) to Adisoetjipto airport is Rp. 3,838.33 per kilometer and is greater than the Willingness To Pay (WTP) for Yogyakarta train services to and from Yogyakarta International Airport Rp. 709 40 per kilometer. Ticket prices are set based on the average price per kilometer of an airport that has a train service amounting to a minimum of Rp 96,644.59.